2017
DOI: 10.3390/ijms18040829
|View full text |Cite
|
Sign up to set email alerts
|

Can Early Rehabilitation Prevent Posttraumatic Osteoarthritis in the Patellofemoral Joint after Anterior Cruciate Ligament Rupture? Understanding the Pathological Features

Abstract: Knee instability resulting from anterior cruciate ligament (ACL) rupture is a high-risk factor for posttraumatic osteoarthritis (PTOA) in the patellofemoral joint (PFJ). However, whether non-weight-bearing and weight-bearing treatments have chondroprotective effects remains unclear. Twenty-four adult New Zealand White male rabbits were employed in this study. All animals received ACL transection in the right knee and sham surgery in the left knee. The rabbits were randomly assigned to the following groups: (I)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Early CPM rehabilitation was investigated over active treadmill exercise due to its potential to decrease the risk of posttraumatic osteoarthritis and to avoid cruciate ligament reconstruction [42]. Also, the evidence indicated that proper rehabilitation exercises benefit the knee joint restoration and improve collagen formation, GAG expression, and bone remodeling [43,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Early CPM rehabilitation was investigated over active treadmill exercise due to its potential to decrease the risk of posttraumatic osteoarthritis and to avoid cruciate ligament reconstruction [42]. Also, the evidence indicated that proper rehabilitation exercises benefit the knee joint restoration and improve collagen formation, GAG expression, and bone remodeling [43,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Clark et al used felines to inspect the histopathological changes in the articular cartilage of the PF joint after ACLT, and showed some erosion at 4 months and loss of proteoglycan staining at 5 years [ 31 ]. Chang et al investigated the histopathological changes after ACLT in rabbits, and reported that OA changes were detected in the superficial and middle zones of the articular cartilage at 4 weeks postoperatively [ 32 ]. Moreover, Tsai et al investigated the histological changes in the PF joint cartilage that resulted in subchondral marrow edema at 16 weeks and matrix degeneration with irregular surfaces at 32 weeks after ACLT in rats [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been previously described animal models of PFJOA. The most thoroughly characterized animal models involving PFJOA is the anterior cruciate ligament transection model in cats [12,14], rabbits [13], and rats [23]. Other surgical models involve changes to muscle strength [24,25] and realignment of the patella [26].…”
Section: Discussionmentioning
confidence: 99%